Cyclic deformation behavior of austenitic Cr–Ni-steels in the VHCF regime: Part II – Microstructure-sensitive simulation. (December 2016) - Hilgendorff, Philipp-Malte; Grigorescu, Andrei Cristian; Zimmermann, Martina; Fritzen, Claus-Peter; Christ, Hans-Jürgen
Highlights: Mesoscopic modeling and simulation of VHCF deformation behavior of Cr–Ni-steels. Plastic deformation in shear bands and deformation-induced martensitic transformation. The model is solved numerically using the 2-D boundary element method. Differences between plastic deformation in AISI 304 and AISI 316 L are revealed. Cyclic softening and hardening characteristics are related to certain mechanisms. Abstract: In Part I – Experimental study, the cyclic deformation behavior of two austenitic stainless steel grades (AISI 304, AISI 316 L) were experimentally investigated at low stress amplitudes in the very high cycle fatigue (VHCF) regime. The observations indicate that during VHCF the metastable austenitic stainless steel (304 grade) performs a pronounced localization of plastic deformation in shear bands followed by a deformation-induced martensitic phase transformation. The 316 grade undergoes only a very limited local plastic deformation in shear bands with almost no phase transformation. Consequently, both materials exhibit distinctly different cyclic softening and hardening characteristics during VHCF. In order to provide a more detailed knowledge about the individual deformation mechanisms and their effect on the cyclic softening and hardening behavior the experimental study is extended by microstructure-sensitive modeling and simulation. Two-dimensional (2-D) microstructures consisting of several grains are represented using the boundary element method and plastic deformation within the microstructure is considered by a mechanism-based approach. Specific mechanisms of cyclic plastic deformation in shear bands and deformation-induced martensitic phase transformation – as documented by experimental results and based on well-known model approaches – are defined and implemented into the simulation. The fatigue behavior at low stress amplitudes observed in experiments can be well represented in simulations so that the underlying model helps to understand the cyclic deformation behavior of austenitic stainless steels at low stress amplitudes in the regime of VHCF strength. In a comparative study based on the resonant behavior the effect of certain deformation mechanisms on the global cyclic softening and hardening characteristics is pointed out for both materials.